Protective Effect of Pediococcus pentosaceus LI05 Against Clostridium difficile Infection in a Mouse Model - Xu, Qiaomai; Gu, Silan; Chen, Yunbo; Quan, Jiazheng; Lv, Longxian; Chen, Dazhi; Zheng, Beiwen; Xu, Lichen; Li, Lanjuan (Frontiers in Microbiology, 2018)
Clostridium difficile infection (CDI) is a major cause of infectious diarrhea among hospitalized patients. Probiotics could be instrumental in restoring the intestinal dysbiosis caused by CDI. Here, we examined the protective effect of Pediococcus pentosaceus LI05 in a mouse CDI model. C57BL/6 mice were administrated P. pentosaceus LI05 (LI05 group) or sterile anaerobic PBS (CDI group) everyday for 14 days. Mice were exposed to antibiotics cocktail; then challenged with C. difficile strain VPI10463. Mice were monitored daily for survival and weight loss. Colonic tissue and serum samples were assessed for intestinal histopathology, intestinal barrier function and systemic inflammation. The oral administration of P. pentosaceus LI05 improved the survival rate and alleviated the histopathological impact of C. difficile. Compared to the CDI group, the levels of inflammatory mediators in the colon as well as inflammatory cytokines and chemokines in serum were substantially attenuated in the LI05 group. P. pentosaceus LI05 alleviated the CDI-induced of disruption of ZO-1, occludin and claudin-1. Additionally, metagenomic sequencing of 16S rRNA gene showed a decrease in pathogenic bacteria abundance like Escherichia. Our results demonstrated that the preventive effect of P. pentosaceus LI05 against CDI was mediated via improving tight junction proteins and down-regulating the inflammatory response. Therefore, P. pentosaceus LI05 could be a promising probiotic in CDI.